Excavations at King's Low and Queen's Low : two early Bronze Age barrows in Tixall, North Staffordshire - Lock, G. R. (Gary R.); Spicer, Dick, 1947-2000; Hollins, Winston (Archaeopress, 2013)
These two barrows in the parish of Tixall, north of Stafford, were excavated by the Stoke-on-Trent Museum Archaeological Society between the years 1986 and 1994. They are approximately one kilometre apart with King's Low still extant but Queen's Low badly damaged by ploughing. The results are important because little excavation of round barrows has been carried out in this area of North Staffordshire and these add considerably to the local corpus of knowledge concerning Early Bronze Age burial practices and various categories of material culture including Collared Urns and a single faience bead at each site.